Utopian Discourses Across Cultures (Peter Lang International Academic Publishers, 2021)
The term Utopia, coined by Thomas More in 1516, contains an inherent semantic ambiguity: it could be read as eu topos (good place) or ou topos (no place). The authors of this volume analyze this polysemous notion and its fascination for scholars across the centuries, who have developed a variety of visions and ways to explain the «realization» of utopian discourses. The experts in the fields of sociology, political science, economics, computer science, literature and linguistics offer extensive studies about how utopian scenarios are realized in different cultural contexts.